Um diálogo entre a formação integral e a educação infantil: aproximações e distanciamentos - Barros, Eva Rodrigues Lopes (Universidade do Vale do Rio dos Sinos, 2020)
This study aims to focus on a dialogue between Integral Formation and kindergarten: approximations and distances aiming to understand the pedagogical conceptions of managers and teachers involved in Kindergarten and its relation with the pedagogical principles and the integrality of the children from zero to five years old. The theoretical foundation of this research is based on authors that dialogue about the conceptions of Kindergarten, childhood and the understanding on caring and educating with actions that benefit their full development. It deals with the role of the management in the teaching and learning processes and the management as the articulator among the physical, material and human aspects, the consolidation of the social role of the school, better understood as a socialization and humanization environment. It discusses integral education and formation as a guarantee for the human development in all their dimensions. It is a methodological research with a qualitative approach whose data collection was through a semi-structured interview with the managers, followed by a questionnaire with the teachers and a document analysis, constituted by the study of the documents from the Jesuit Education Network and national documents. The research was carried out in three schools from the Jesuit Education Network in the three regions of Brazil where the Jesuit Networks is. From the results got in this research on the conceptions of Kindergarten, child and childhood, the BNCC relationship and the Ignatian Pedagogy, it was shown that the research participants aired knowledge related to the need and benefits of the Integral Education for the human being formation. They also showed to understand that the environment is essential for the development of the practice in the Integral Formation outlook, although there is a clear distinction between the understanding of the management (collected through the interviews) and the teachers (got from the questionnaires) regarding the conception of childhood and the importance of playful activities in this phase of life. As an intervention proposal, it was made pedagogical indications for kindergarten with focus on BNCC, childhood and play as opportunities of an integral education and the humanist formation. It can be concluded that the development of formation which focus on the use of playful activities is important to promote the children development and on the role of Kindergarten for childhood, favoring the children learning in all their dimensions.
Keywords: Formação Integral; Educação Infantil; Concepções pedagógicas; Pedagogia Inaciana; Infância e gestão; Integral formation; Kindergarten; Pedagogical conceptions; Ignatian pedagogy; Childhood and management; ACCNPQ::Ciências Humanas::Educação